Highly cited article - Savva, Christos S. (My University, 2026)
Stock market integration between new EU member states and the Euro-zone Published in: Empirical Economics, Volume 39, Issue Number 2, October 2010, pages 337–351 is among the most cited articles published by Empirical Economics, it is currently ranked number 51 most cited articles in this journal according to Web of Science by Clarivate. We would like to extend our best wishes for your continued success and hope you enjoyed working with Empirical Economics.
Keywords: Social sciences